PEMBELAJARAN FISIKA DENGAN MODEL LEARNING CYCLE 7E PADA MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN KETERAMPILAN PROSES SISWA KELAS X SMA NEGERI 4 PEKANBARU - Riza Ambar Rani; Nurislami '; Azhar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research is aimed to describe and differentiate the process skill through the implementation of learning cycle 7E model for the material dynamic electricity in the class of X SMA Negeri 4 Pekanbaru. Population in this research is all of X classes which consist 9 classes. Meanwhile the samples are 37 students in X3 as experimental class and 37 students in X4 as control class. The instrument of data collection in this study is a process skill performance test which consists of 10 multiple choice items. The research instrument used is Physics process skills achievement test array of aspect: observing, predicting, planning experiment, applying concept and concluding. Data were analyzed by descriptive and inferential methods. Descriptive analysis of student’s process skill after learning with implementation of Learning Cycle 7E model is 86,15% of the good category and declared effective learning efficiently. The value of t tests is p = 0.010 means p < 0.050, then H0 is rejected. Which means that there are differences in process skill test result between students in experiment class that taught using learning cycle 7E and control class that uses conventional learning with a level of 95%. It can therefore be concluded that the implementation of learning cycle 7E can be used as an alternative in the learning process in the classroom X SMA Negeri 4 Pekanbaru.Key Words: Learning cycle 7E, Process Skill, Dinamyc Electricity